Effects of Micronutrients (B, Cu , Fe, Mn, Mo, Zn) on Plant Performance and Yield of Pineapple CVS Mauritius and Masmerah Planted on Malaysian Virgin Peat Soils - Mohamad, Ramlah (1982)
The objective of this study is to establish the importance of micronutrients B, Fe, Mn, Mo and especially Cu and Zn for the cuItivation of pineapple cvs Mauritius and Masmerah on virgin peat coils in Peninsular Malaysia. A pot and three field trials were set up to determine the effects of these micronutrients on the plant height, leaf number, fresh and dry weights of D-leaf, Cu and Zn content of D-leaf and the fruit weight of these two cultivars. The deficiency symptoms were also observed. A study on rinduced Cu and Zn deficiencies was also carried out on the two cultivars. Only Cu showed distinct deficiency symptoms in both the pot and field trials in pineapple cv Mauritius while none was observed for B, Fe, Mn, Mo,and Zn. No distinct deficiency symptoms of B, Cu, Fe, Mn, Mo and Zn were observed on pineapple cv Masmerah. only Cu was observed to give significant effect to the plant height, fresh an d dry weight of D-leaf an d Cu-content of D-leaf on cv Mauritius. However, the leaf number and fruit weight were not significantly affected. The Cu-deficient pl ants in the field were observed to be sporadic or pocket-like in distribution . The deficiency was observed to occur as early as the fourth of fifth month of planting. No significant difference was observed with the different levels of Cu (5,10,15 kg/ha) applied on the above-mentioned factors investigated. Thus, Cu at 5 kg/h a would be sufficient to overcome the deficiency symptoms in the field. The effect of Zn was observed to be non-significant for the cultivation of pineapple cv Mauritius.